BUSINESS DEVELOPMENT BASED ON VOICE OF CUSTOMER SYSTEM TO IMPROVE SERVICE QUALITY IN CULINARY BUSINESSES - Julita Nanna; Muhammad Rakib; Agus Syam (Adiba Aisha Amira, 2025)
This research aims to improve the quality of service in the culinary business (Business